Airway pathogens detected in stable and exacerbated COPD in patients in Asia-Pacific. Issue 3 (26th September 2022) - Taddei, Laura; Malvisi, Lucio; Hui, David S.; Malvaux, Ludovic; Samoro, Ronnie Z.; Lee, Sang Haak; Yeung, Yiu Cheong; Liu, Yu-Chih; Arora, Ashwani Kumar
Background: The burden of chronic obstructive pulmonary disease (COPD) in the Asia-Pacific region is projected to increase. Data from other regions show bacterial and viral infections can trigger acute exacerbations of COPD (AECOPD). Methods: This 1-year prospective epidemiological study (ClinicalTrials.gov identifier: NCT03151395) of patients with moderate to very severe COPD in Hong Kong, the Philippines, South Korea and Taiwan assessed the prevalence in sputum samples (by culture and PCR) of bacterial and viral pathogens during stable COPD and AECOPD. The odds of experiencing an exacerbation was evaluated for pathogen presence, acquisition and apparition. Health-related quality of life (HRQOL) was assessed. Results: 197 patients provided 983 sputum samples, with 226 provided during exacerbation episodes. The mean yearly AECOPD incidence rate was 1.27 per patient. The most prevalent bacteria by PCR at exacerbation were Haemophilus influenzae (Hi) and Moraxella catarrhalis (Mcat); Mcat prevalence was higher at exacerbation than at stable state. Virus prevalence was low, other than for human rhinovirus (HRV) (8.1%, stable state; 16.6%, exacerbation). The odds ratio (95% CI) for an exacerbation ( versus stable state) was statistically significant for the presence, acquisition and apparition of Hi (2.20, 1.26–3.89; 2.43, 1.11–5.35; 2.32, 1.20–4.46, respectively), Mcat (2.24, 1.30–3.88; 5.47, 2.16–13.86; 3.45, 1.71–6.98, respectively) and HRV (2.12, 1.15–3.91; 2.22, 1.09–4.54; 2.09, 1.11–3.91, respectively). HRQOL deteriorated according to the number of exacerbations experienced. Conclusion: In patients with COPD in the Asia-Pacific region, the presence of Hi, Mcat or HRV in sputum samples significantly increased the odds of an exacerbation, providing further evidence of potential roles in triggering AECOPD. The presence of Haemophilus influenzae, Moraxella catarrhalis or human rhinovirus in sputum samples significantly increases the odds of an exacerbation, as opposed to being in stable state, in COPD https://bit.ly/39vI3XU